HASHTAG #WISATAVIRTUAL PADA INSTAGRAM SEBAGAI INFORMASI WISATA SAAT PANDEMI COVID-19 - Hendi Prasetyo; Anik Nur Azizah (Kepariwisataan: Jurnal Ilmiah, 2021)
This study aims to determine the hashtag #wisatavirtual on Instagram as travel information during the Covid-19 pandemic. Researchers used descriptive qualitative research methods using literature study and document techniques. The results of this study indicate that Instagram is a social media that can be used as information for its users. One of the information that can be found on Instagram during the Covid-19 pandemic is the hashtag #wisatavirtual. Based on the search results, researchers found the number of posts related to #wisatavirtual 1000+ posts that can be grouped into top and recent posts. Most of the information shows about alternatives to travel during the Covid-19 pandemic, virtual tour schedules, a variety of information related to virtual travel invitations to various tourist destinations. In addition, other information obtained from searches about #wisatavirtual is related to general information about virtual tourism. The results of searches that have been carried out by researchers also show that there are posts that are not related (not relevant) to virtual tourism, but these posts include # toursvirtual in their posts. The existence of #wisatavirtual has shown the existence and trend of posts on Instagram related to #wisatavirtual carried out by its users. In addition, Instagram posts with #wisatavirtual also get good responses from Instagram users.Keywords: #wisatavirtual, Information, Covid-19